Relationships between care burden, resilience, and depressive symptoms among the main family caregivers of stroke patients: A cross-sectional study - Fang, Linlin; Dong, Mengyuan; Fang, Wenbo; Zheng, Jin (Frontiers in Psychiatry, 2022)
Objectives This study aims to explore the potential mediating role of resilience between care burden and depressive symptoms in family caregivers of stroke patients. Methods A cross-sectional study was conducted with a convenience sample involving 245 main family caregivers of stroke patients recruited from the neurology department of a Tertiary A hospital in China. Mediation analyses were conducted using the PROCESS macro (Model 4) for SPSS, applying the Bootstrap analysis with 5,000 samples and a 95% confidence interval. Results The results showed that with constant hemiplegia side, Barthel Index, education level, monthly income, care time per day, and living with patients in regression equations, the resilience partially mediated the correlation of care burden and depressive symptoms with a mediation effect ratio of 26.32%. Conclusions Resilience plays a mediating role in the correlation between care burden and depressive symptoms. Impact The findings indicated a protective effect of resilience in alleviating the negative influences of care burden on depressive symptoms, suggesting that resilience-training intervention may be developed to mitigate depressive symptoms of the main family caregivers of stroke patients.